Analysis of village fund allocation management in kaur district year 2021 (Study in Guru Agung 1 Village, North Kaur District, Kaur Regency, Bengkulu Province) - Deky Akbar; Bobby Mandala Putra; Heru Purnawan; Supriyono Supriyono; Ade Fitrah Putra Akhir; Parwito Parwito; Janusi Waliamin (GAYAKU PUBLISHER, 2022)
The purpose of this study is to find out how to manage the allocation of village funds in Guru Agung I Village in 2021. The research methods are interviews, documentation, and observation. The results of the research on Analysis of the Management of Village Fund Allocation in Kaur Regency (Study in Guru Agung Village, North Kaur District, Kaur Regency, Bengkulu Province), show that: 1) The planning stage of Village Fund Allocation in Guru Agung Village applies the principle of transparency. 2) At the stage of implementing ADD, Guru Agung village carried out self-management because the village government also wanted to improve the welfare of the community. 3) The stage of ADD accountability in Guru Agung Village, both technically and administratively, is good. Conclusion The Village Fund Allocation Management (ADD) carried out by the village government of Guru Agung I, North Kaur District, Kaur Regency has followed the guidelines in the legislation. The village government has implemented the principles of managing the Village Fund Allocation